Nuclear-encoded factors associated with the chloroplast transcription machinery of higher plants - Yu, Qing-Bo (Frontiers Media S.A., 2014)
Plastid transcription is crucial for plant growth and development. There exist two types of RNA polymerases in plastids: a nuclear-encoded RNA polymerase (NEP) and plastid-encoded RNA polymerase (PEP). PEP is the major RNA polymerase activity in chloroplast. Its core subunits are encoded by the plastid genome, and these are embedded into a larger complex of nuclear-encoded subunits. Biochemical and genetics analysis identified at least 12 proteins are tightly associated with the core subunit, while about 34 further proteins are associated more loosely generating larger complexes such as the transcriptionally active chromosome (TAC) or a part of the nucleoid. Domain analyses and functional investigations suggested that these nuclear-encoded factors may form several functional modules that mediate regulation of plastid gene expression by light, redox, phosphorylation, and heat stress. Genetic analyses also identified that some nuclear-encoded proteins in the chloroplast that are important for plastid gene expression, although a physical association with the transcriptional machinery is not observed. This covers several PPR proteins including CLB19, PDM1/SEL1, OTP70, and YS1 which are involved in the processing of transcripts for PEP core subunit as well as AtECB2, Prin2, SVR4-Like, and NARA5 that are also important for plastid gene expression, although their functions are unclear.